Strategi Guru Dalam Meningkatkan Pemahaman Peserta Didik Terhadap Pembelajaran Al-Qur’an Hadits Di MTs Ittihaadul Ulum Lubuklinggau - Johan Effendi; Yunardi Ihsan; Aldo Yolanda; Penia Ulandari; Nuriza Aulia; Mirzon Daheri (Edification Journal : Pendidikan Agama Islam, 2026)
This study aims to describe teachers’ strategies in improving students’ understanding of Al-Qur’an Hadith learning at MTs Ittihaadul Ulum Lubuklinggau. The background of this research stems from the challenge of low interest and comprehension among students regarding Al-Qur’an Hadith material, which requires innovative teaching strategies. The research method employed is descriptive qualitative, with data collected through observation, interviews, and documentation. The findings reveal that teachers apply several strategies, including interactive lectures, group discussions, visual media-based learning, as well as assignments involving memorization and contextual interpretation of verses. These strategies have proven effective in enhancing students’ active engagement, strengthening memory retention, and fostering religious attitudes in daily life. The conclusion emphasizes that the success of Al-Qur’an Hadith learning is strongly influenced by teachers’ creativity in selecting and combining strategies that align with students’ characteristics.